Acquired factor V inhibitor in a case of pediatric venous thrombosis - Sweta Gupta; Matthew W. Bunce; Emily A. Cid; Rodney M. Camire; Amy D. Shapiro (Research and Practice in Thrombosis and Haemostasis)
Background: The development of acquired factor (F)V with inhibitor (AFVwI) is rare, resulting mainly in bleeding complications, although sporadic cases of thrombosis in adults have been reported. Key Clinical Question: How do you diagnose and manage a pediatric case of acute deep venous thrombosis associated with the concurrent finding of AFVwI? Clinical Approach: A 13-year-old female with Crohn's Disease and May–Thurner anatomy developed extensive deep venous thrombosis of the left lower extremity, complicated by the finding of AFVwI, discovered during the evaluation of a prolonged prothrombin time and a low FV activity. Anticoagulation was initiated with low-molecular-weight heparin followed by a direct oral anticoagulant, rivaroxaban, without any complications. AFVwI was undetectable after 5 months with normalization of FV activity. Conclusion: Our case highlights the first pediatric case of thrombosis with a rare finding of AFVwI, successfully managed with anticoagulation therapy with complete resolution.